Comparative Sequence Analysis, Pathogenicity and Immunogenicity of Attenuated Fowl Adenovirus Isolates as Experimental Vaccines against Inclusion Body Hepatitis of Commercial Broiler Chickens - NORFITRIAH MOHAMED SOHAIMI; Mohd Hair-Bejo (Vaccine Research, 2021)
Introduction: Fowl adenoviruses (FAdV) cause inclusion body hepatitis (IBH) in chickens and new vaccination strategies against IBH are needed as an effective control measure in the poultry industry. Methods: The attenuated FAdV isolates from from chicken embryonated (UPM1137E20) and cell culture (UPM1137CEL35) were evaluated and compared based on sequence analysis of hexon and fiber genes. Their pathogenicities and immunogenicities were then determined in the commercial broiler chickens. Groups of chicken were inoculated with 0.5ml chicken-embryonated-derived attenuated FAdV isolates via oral and IP routes and sera, trachea, liver and gizzard samples were collected at days 3, 7, 14 and 21post-inoculation. Results: Molecular analysis revealed both isolates had 99.1% and 97.3% homologies in the L1 loop region of hexon gene and knob region of fiber gene, respectively. Molecular changes in UPM1137E20 were prominent in the knob of fiber gens with 3 amino acid changes, while for UPM1137CEL35, notable in the L1 loop region with 3 amino acid changes. It was demonstrated that both attenuated isolates are non-pathogenic and safe in commercial broiler chickens. Neither gross nor histopathological lesions were recorded in all tested groups. Both isolates induced high antibody response significantly via intraperitoneal route when compared to the control. Conclusion: UPM1137E20 isolate had a high potential to be further evaluated as a live attenuated vaccine against viral poultry diseases such as IBH.